Maternal Health Education in the Digital Era: Opportunities and Challenges - Febriani, Isyfi Salwa (Yayasan Sinergi Kawula Muda, 2022)
Maternal health education is a key determinant in improving maternal and neonatal outcomes. This study explores the effectiveness of community-based interventions and digital health tools in enhancing maternal knowledge and healthcare utilization. A systematic review was conducted using data from reputable databases to assess the impact of various maternal health education programs across different socio-economic and cultural contexts. Findings indicate that community-based maternal health education significantly improves knowledge retention and antenatal care adherence, while digital health tools enhance accessibility and engagement. However, socio-economic disparities, digital literacy limitations, and cultural norms hinder equitable access to maternal health information. Addressing these challenges requires integrated policy approaches, increased investment in healthcare infrastructure, and targeted digital literacy programs. This study underscores the need for sustainable maternal health education initiatives, combining technology with traditional health interventions. Future research should focus on assessing the long-term effects of digital health education, exploring artificial intelligence applications, and involving male partners in maternal health programs. Strengthening these efforts can contribute to a substantial reduction in maternal and neonatal mortality rates, particularly in resource-limited settings.